Association of C-reactive protein and non-steroidal anti-inflammatory drugs with cardiovascular events in patients with psoriatic arthritis: a time-dependent Cox regression analysis. (June 2021) - Lam, Steven H.; So, Ho; Cheng, Isaac T.; Li, Edmund K.; Wong, Priscilla; Li, Tena K.; Lee, Alex Pui-Wai; Tam, Lai-Shan
Aims: Psoriatic arthritis (PsA) is associated with accelerated atherosclerosis due to underlying inflammation. Whether inflammatory burden and drugs used to suppress inflammation over time are associated with cardiovascular (CV) events remained unclear. This study aims to examine the time-varying effect of C-reactive protein (CRP) levels and the use of drugs, including non-steroidal anti-inflammatory drugs (NSAIDs) and disease modifying anti-rheumatic drugs, on the risk of CV events independent of traditional CV risk factors in PsA patients. Methods: A retrospective cohort analysis was performed in patients with PsA who were recruited from 2008 to 2015 and followed until the end of 2019. The outcome was occurrence of a first CV event. Framingham risk score (FRS) was used to quantify the traditional CV risk. Cox proportional hazard models with time-varying CRP levels and drugs used were analysed to identify the risk factors for CV events in PsA patients. Results: Two hundred patients with PsA [median age: 47.5 (40.0–56.0); male: 119 (59.5%)] were recruited. After a mean follow-up of 8.8 ± 3.8 years, 30 (15%) patients developed a first CV event. The multivariable Cox regression model showed that time-varying CRP level [hazard ratio (HR) 1.02, 95% confidence interval (CI) 1.00–1.04] and NSAIDs exposure (HR 0.38, 95% CI 0.15–0.96) were significantly associated with CV events after adjusting for baseline FRS (HR 5.06, 95% CI 1.84–13.92). Conclusion: Increased inflammatory burden as reflected by elevated CRP level was associated with increased risk of CV events, while the risk was significantly reduced with NSAIDs use in PsA patients.